2006
DOI: 10.1021/ac052171y
|View full text |Cite
|
Sign up to set email alerts
|

Nanomechanical Detection of DNA Melting on Microcantilever Surfaces

Abstract: We observe surface stress changes in response to thermal dehybridization, or melting, of double-stranded DNA (dsDNA) oligonucleotides that are grafted on one side of a microcantilever beam. Changes in surface stress occur when one complementary DNA strand melts and diffuses away from the other, resulting in alterations of the electrostatic, counterionic, and hydration interaction forces between the remaining neighboring surface-grafted DNA molecules. We have been able to distinguish changes in the melting temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 42 publications
2
52
0
Order By: Relevance
“…A similar effect was discussed by Majumdar et al, who applied nanomechanical detection of DNA melting on microcantilever surfaces and also observed lower melting temperatures for the surface confined duplexes [33]. Using covalent ferrocene labels, Hartwich et al also found similar melting behavior [34].…”
Section: Resultssupporting
confidence: 66%
“…A similar effect was discussed by Majumdar et al, who applied nanomechanical detection of DNA melting on microcantilever surfaces and also observed lower melting temperatures for the surface confined duplexes [33]. Using covalent ferrocene labels, Hartwich et al also found similar melting behavior [34].…”
Section: Resultssupporting
confidence: 66%
“…In recent years a versatile platform for biodetection has been developed based on microfabricated arrays of silicon cantilevers 14,15,16,17,18,19,20,21 , each coated with a sensitive layer for molecular recognition, e.g. a gene specific oligonucleotide.…”
mentioning
confidence: 99%
“…3c) ). Such nanomechanical biosensors can be used for applications in ultrasensitive detection of: DNA hybridization (Biswal et al 2006;Fritz et al 2000), biomarker transcripts in human RNA , and viruses (Gupta et al 2006). In addition, cantilever-based force spectroscopy has emerged as a powerful tool for characterizing spatiotemporal dynamics of the interaction between individual ligands and receptors, either on isolated molecules or on cellular surfaces (Hinterdorfer and Dufrene 2006), such as VEGFR2 (Lee et al 2007b) or integrin a2b1 (Taubenberger et al 2007).…”
Section: Cantilever-based Biosensorsmentioning
confidence: 99%